Primary Tumor Resection for Rectal Cancer With Unresectable Liver Metastases: A Chance to Cut Is a Chance for Improved Survival - Chen, Jia-nan; Shoucair, Sami; Wang, Zheng; Habib, Joseph R.; Zhao, Fu-qiang; Yu, Jun; Liu, Zheng; Liu, Qian (Frontiers in Oncology, 2021)
ABSTRACT Background About half of the patients with rectal cancer will develop liver metastasis during the course of their illness. Unfortunately, a large proportion of these metastases are unresectable. Surgical resection of the primary tumor versus palliative treatment in patients with unresectable synchronous liver metastases remains controversial. Methods Patients with rectal cancer with surgically unresectable liver metastases were identified from the Surveillance, Epidemiology, and End Results (SEER) database from January 1, 2010, to December 31, 2015. According to different treatment modalities, patients were divided into a primary tumor resection group and a non-resection group. Rates of primary tumor resection and survival were calculated for each year. Kaplan–Meier methods and Cox regression models were used to assess long-term survival. Multivariable logistic regression models were used to evaluate factors potentially associated with primary tumor resection. Results Among 1,957 patients, 494 (25.2%) had undergone primary tumor resection. Patients with primary tumor resection had significantly better 5-year survival rate (27.2% vs 5.6%, P < 0.001) compared to the non-resection group. Chemoradiotherapy with primary site resection was associated with the longest mean and 5-year OS (44.7 mons, 32.4%). The Cox regression analyses of the subgroup indicated that patients who underwent primary tumor resection had improved survival compared with those who did not undergo resection in all 25 subgroups. Factors associated with primary tumor resection were well or moderately differentiated tumor grade, undergoing radiation, and primary tumor size < 5cm. Conclusions The majority of patients with rectal cancer with unresectable liver metastases did not undergo primary tumor resection. Our results indicate that resection of the primary tumor appears to offer the greatest chance of survival.